Prabowo Subianto’s Leadership in His Speech at the 80th UN General Assembly: A Rhetorical Analysis of Ethos, Pathos, and Logos - Giovannesandesva Hendri; Hasnah Faizah (International Journal of Social Science and Humanity, 2025)
State speeches in international forums are a strategic arena for the practice of diplomacy and leadership image management. This study analyzes President Prabowo Subianto's rhetorical style in his speech at the 80th UN General Assembly on September 23, 2025. Using Aristotelian theory, namely ethos, pathos, and logos, to understand how rhetoric functions in strengthening political legitimacy, humanitarian solidarity, and international policy arguments. Using a qualitative-descriptive approach, this study examines transcripts of official speeches and identifies quotations that represent each persuasive mode. The analysis shows that Prabowo builds ethos through historical references, concrete actions of Indonesia such as the contribution of peacekeeping troops, and pathos is depicted through narratives of suffering, calls for solidarity, and an emphasis on the future of the younger generation; while logos is demonstrated through the presentation of data, policy plans such as the net-zero target, technical solutions such as sea walls, and systematic cause-and-effect arguments. This combination of ethos, pathos, and logos confirms that the speech was not simply a policy statement but also a rhetorical diplomatic tool that strengthened Indonesia's image as a constructive global actor. These findings contribute to the study of leadership communication and diplomatic rhetoric, particularly in the context of developing countries seeking to enhance the role of multilateralism and soft power.